Franz Peter Schubert the greatest love and the greatest sorrow - Ashkenazy, Vladimir 1937-; Schmidt, Andreas 1960-; Weithaas, Antje; Sanderling, Michael; Sawallisch, Wolfgang 1923-2013; Nupen, Christopher; Nupen, Christopher; Schubert, Franz 1797-1828
Franz Schubert's reputation suffered from the fact that he did things differently, and when a work of art is new and different, and the world cannot categorise or label it, it often takes a long time for the world to understand and accept what that work has to offer. In some ways, these things haunt Schubert's reputation even today. To complicate the picture still further, Schubert lived, and in some ways his music continues to live, under the shadow of Beethoven. Schubert himself asked the question "Wer vermag nach Beethoven noch etwas zu machen?" (Who would dare to do anything after Beethoven?). The answer, of course, was Franz Peter Schubert and, most notably, in the music that he wrote after the death of his God, Ludvig van Beethoven. The title of this film is drawn from a dream which Schubert wrote down, in detail, on the 3rd of July, 1822 and which is quoted in full in the film
Title from resource description page (viewed Jul. 25, 2014)
Keywords: Schubert, Franz / 1797-1828; Documentary films; Streaming videos